Multi-version consolidation method for block-level backup data - WANG Shu-peng 1; WU Guang-jun1; WU Zhi-gang3; YUN Xiao-chun1 (Tongxin xuebao, 2011)
Historical version backup data query efficiency was dependent on the version chain length in a multi-version backup data storage system.A novel block-level backup data multi-version consolidation method was presented for this problem.Any version of a historical full system snapshot could be generated within the incremental backup data version sequence.Theoretical analysis showed that it could increase the target snapshot version query efficiency significantly in the version chain.A variable-length block version merging algorithm was presented to decrease the computing complex-ity in the process of snapshot version merging,according to the block-level backup data distribution features.Finally,the concrete applications and performance analysis for block-level version consolidation method was also introduced.The simulated experiments results expose that the version consolidation method can eliminate redundant version of backup data with the same version chain length,and it can increase full system recovery efficiency than traditional methods sig-nificantly.